Targeting CD8 T-Cell Metabolism in Transplantation - Yap, Michelle; Brouard, Sophie; Pecqueur, Claire; Degauque, Nicolas (Frontiers in Immunology, 2015)
Infiltration of effector CD8 T cells play a major role in allograft rejection, and increases in memory and terminally-differentiated effector memory (TEMRA) CD8 T cells are associated with long term allograft dysfunction. Alternatively, CD8 regulatory T (Tregs) cells suppress the inflammatory responses of effector lymphocytes and induce allograft tolerance in animal models. Recently, there has been a renewed interest in the field of immunometabolics and its important role in CD8 function and differentiation. The purpose of this review is to highlight the key metabolic pathways involved in CD8 T cells and to discuss how manipulating these metabolic pathways could lead to new immunosuppressive strategies for the transplantation field.